2001
DOI: 10.1038/sj.onc.1204972
|View full text |Cite
|
Sign up to set email alerts
|

Cell density mediated pericellular hypoxia leads to induction of HIF-1α via nitric oxide and Ras/MAP kinase mediated signaling pathways

Abstract: Environmental signals in the cellular milieu such as hypoxia, growth factors, extracellular matrix (ECM), or cell-surface molecules on adjacent cells can activate signaling pathways that communicate the state of the environment to the nucleus. Several groups have evaluated gene expression or signaling pathways in response to increasing cell density as an in vitro surrogate for in vivo cell-cell interactions. These studies have also perhaps assumed that cells grown at various densities in standard in vitro incu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
103
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(110 citation statements)
references
References 60 publications
7
103
0
Order By: Relevance
“…Upregulation of COX-2 expression in NIH3T3 cells due to the hypoxic condition It has been reported that increasing epithelial cell density results in pericellular hypoxia (Tokuda et al, 2000;Sheta et al, 2001), and hypoxia has been reported to induce COX-2 expression in endothelial cells (Schmedtje et al, 1997;Xu et al, 2000;Wu et al, 2003). Therefore, we next examined whether hypoxia can modulate COX-2 expression in NIH3T3 cells.…”
Section: Resultsmentioning
confidence: 99%
“…Upregulation of COX-2 expression in NIH3T3 cells due to the hypoxic condition It has been reported that increasing epithelial cell density results in pericellular hypoxia (Tokuda et al, 2000;Sheta et al, 2001), and hypoxia has been reported to induce COX-2 expression in endothelial cells (Schmedtje et al, 1997;Xu et al, 2000;Wu et al, 2003). Therefore, we next examined whether hypoxia can modulate COX-2 expression in NIH3T3 cells.…”
Section: Resultsmentioning
confidence: 99%
“…2C). Normoxic stabilization of Hif-1␣ has been reported previously and has been correlated with cell culture confluency (58). Given the nature of epithelial growth displaying high cell-to-cell contact, we feel that this normoxic level of Hif-1␣ is representative of normal epithelial cell cultures.…”
Section: Conditional Targeting Of Hif-1␣ In Ptcsmentioning
confidence: 98%
“…Cell density has actually been shown to induce HIF-1a (22), and a computer analysis of human 4E-BP1 gene sequence revealed the presence of a putative HRE located in the À278/þ64 4E-BP1 promoter segment (Fig. 4A) that mediates cell density-dependent activation of 4E-BP1 promoter.…”
Section: Sst2-and Cell Density-triggered Accumulation Of 4e-bp1 Is Dementioning
confidence: 99%